2016
DOI: 10.1186/s13717-016-0060-6
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater recharge rates and surface runoff response to land use and land cover changes in semi-arid environments

Abstract: The effects of land use and land cover (LULC) on groundwater recharge and surface runoff and how these are affected by LULC changes are of interest for sustainable water resources management. However, there is limited quantitative evidence on how changes to LULC in semi-arid tropical and subtropical regions affect the subsurface components of the hydrologic cycle, particularly groundwater recharge. Effective water resource management in these regions requires conclusive evidence and understanding of the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
68
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(71 citation statements)
references
References 78 publications
(61 reference statements)
2
68
0
1
Order By: Relevance
“…As mentioned in Section , grassland produces an overall flow regime moderation (e.g., Owuor et al, ; Weaver and Noll, 1935; Schilling et al, ); thus, the Indicators of Hydrologic Alteration (IHA) software (The Nature Conservancy, ) was used to evaluate high‐ and low‐flow regimes in addition to mean flow regimes of grassland–cropland land conversion. SWAT model outputs for the simulated scenarios including the baseline scenario were then processed with IHA software (The Nature Conservancy, ) to compute 10 major streamflow statistics to illustrate low (drought) and high‐flow regimes (flood) and determine the magnitude and duration of annual water conditions at the outlet of the watershed (The Nature Conservancy, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned in Section , grassland produces an overall flow regime moderation (e.g., Owuor et al, ; Weaver and Noll, 1935; Schilling et al, ); thus, the Indicators of Hydrologic Alteration (IHA) software (The Nature Conservancy, ) was used to evaluate high‐ and low‐flow regimes in addition to mean flow regimes of grassland–cropland land conversion. SWAT model outputs for the simulated scenarios including the baseline scenario were then processed with IHA software (The Nature Conservancy, ) to compute 10 major streamflow statistics to illustrate low (drought) and high‐flow regimes (flood) and determine the magnitude and duration of annual water conditions at the outlet of the watershed (The Nature Conservancy, ).…”
Section: Methodsmentioning
confidence: 99%
“…When cultivated cropland are converted from forestland and grassland, ET generally tends to decrease, providing opportunity for more water to percolate down and contribute to groundwater recharge (e.g., Adane, Nasta, Zlotnik, & Wedin, ; Owuor et al, ; Scanlon, Jolly, Sophocleous, & Zhang, ), thus leading to downstream flow moderation. Field experiments demonstrated that grassland depletion contributes to changes in hydrologic processes such as ET, run‐off, soil moisture, and infiltration (Fiedler, Frasier, Ramirez, & Ahuja, ; Li et al, ), which are, in turn, influenced by inherent soil properties, land use and land cover patterns, the initial moisture condition, and rainfall patterns (Agnihotri & Yadav, ).…”
Section: Introductionmentioning
confidence: 99%
“…24 A review of land cover relation to groundwater in Ref. 25 revealed a need for site-specific groundwater monitoring networks due to the highly varied environmental and geological landscapes of Africa. The importance of the land use-groundwater relation is emphasized due to the increased demand for water to meet the needs of the rising population.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of the land use-groundwater relation is emphasized due to the increased demand for water to meet the needs of the rising population. 25 In this study, analysis of multispectral imagery (RapidEye, Landsat, and Sentinel-2 images spanning from 2013 to 2016) was conducted to map seasonal land cover variability. The selected optical images played complimentary roles as RapidEye has a high spatial resolution but is costly while Sentinel-2 and Landsat-8 data are both freely accessible.…”
Section: Introductionmentioning
confidence: 99%
“…Land-use changes may modify recharge rates and affect groundwater resources (Foley et al, 2005;Lerner and Harris, 2009;Owuor et al, 2016). In many semi-arid regions, there has been the conversion of native forests to agricultural land (Foley et al, 2005).…”
mentioning
confidence: 99%